(untitled) (Research, Society and Development, 2020)
Unlike pressure or temperature, the concept of entropy, while sharing abstraction and importance similar to the concept of energy, clash of the last for not being intuitive, in addition to the ambiguity historically linked to it due to developments related to the Thermodynamics second’s Law. In this work, we seek to promote a reflection on the existing discrepancies around the conceptualization of entropy in terms of disorder and its impacts on the learning process at all levels of teaching, listing other conceptual possibilities, among which Shannon’s entropy, seen as more adequate to represent the entire body of multidisciplinary knowledge arising from information theory, including quantum computing. The work takes into account the publications of the Israeli chemist Arieh Ben Naim and, taking advantage of the lack of other possible analogies for entropy in Brazilian literature, proposes an exhibition that contemplates the different perspectives around the theme as a bias towards a meaningful learning and therefore adapting all levels of education to maintain formalism (still phenomenological) of thermodynamics in line with the (new) Quantum Thermodynamics and with the current interdisciplinary approach to entropy.